Evaluation of using probiotics, prebiotics and symbiotic as growth promoters in broilers and their effects on some growth performance-related genes - El-kahal Hassanien, A; EL-Kaiaty, AM; Sobhy, HM; El Moghazy, GM; Gomaa, AH; Abdel A’al, MH; EL-Attrouny, MM; Hekal, SHA (Journal of the Hellenic Veterinary Medical Society, 2024)
This study was conducted in an attempt to evaluate the impact of dietary addition of probiotics (Enterococcus faecium, Lactobacillus acidophilus, Bacillus subtilis and Saccharomyces cerevisiae) and prebiotics (beta glucan and mannan oligosaccharides) on broiler diets with respect to some growth related genes (mucin2, chicken growth hormone (cGH), and insulin-like growth factor-1 (IGF-1) gene expressions. It was also our aim to evaluate the growth performance and economic efficiency of the diet. A total of 350 one-day male broiler chicks (ROSS) were randomly divided into 14 groups each group contained 25 birds were fed different doses of probiotics, prebiotics and symbiotic except the control group. The results showed that there was a significant improvement in body weight gain (BWG) of the treatments fed on probiotics, prebiotics and symbiotic compared to the control group. The best result was T8, 2007.5± 23.88 which contains Probiotics (108 cfu / ml) + 250 ppm prebiotics/ ton. The same treatment (T8) also showed a clear improvement in feed intake (FI), as the birds consumed the least amount of feed 3064± 26.53 compared to other groups with the best feed conversion rate 1.52± 0.01. The liver of birds fed T8 had higher IGF1 and cGH expression compared to other treatments 7.60±1.33 and 8.66±1.38 respectively. Enhanced expression of the muc2 was found in treatments fed on probiotics, prebiotics and symbiotic, the best result was T8 8.70±1.29. The economic evaluation showed that birds fed on symbiotic at a 250 ppm level of prebiotics was the best treatments. It could be concluded that supplementation with probiotics, prebiotics, and symbiotic had beneficial effects on total BWG, FI, FCR and IGF1, cGH and muc2 expression in broiler chickens. They also enhanced the expression of some growth-related genes, so they can be used as an alternative to antibiotics.